2023
DOI: 10.1002/jbio.202300083
|View full text |Cite
|
Sign up to set email alerts
|

Dose and time–response effect of photobiomodulation therapy on glycemic control in type 2 diabetic patients combined or not with hypoglycemic medicine: A randomized, crossover, double‐blind, sham‐controlled trial

Clara Maria Cobra Branco Scontri,
Flávio de Castro Magalhães,
Ana Paula Moraes Damiani
et al.

Abstract: Photobiomodulation therapy (PBMt) combined or not with oral hypoglycemic medication has not been investigated in type 2 diabetes (T2DM) patients. All 10 T2DM patients were assessed randomly at 6 different occasions (3 with and 3 without regular oral hypoglycemic medication). Capillary glycemia was assessed after overnight fast (pre‐prandial), 1 h postprandially (standardized meal, 338 kcal), and 30 min, 3 h, 6 h, 12 h post‐PBMt (830 nm; 25 arrays of LEDs, 80 mW/array). Three doses (0 J—sham, 100 J, 240 J per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…A total of 9 studies were conducted, with 8 studies conducted on preclinical models ( 70 78 ) and one study in humans ( 79 ) ( Table 4 ). The preclinical studies consistently reported positive effects of PBM on metabolic parameters with an improvement in glucose tolerance [with a glucose tolerance test area under the curve (GTT AUC) decreasing by 12–28%], a decrease in insulin resistance [with a 22% decrease in homeostatic model assessment of insulin resistance (HOMA-IR ( 70 )) and a 10% decrease in insulin tolerance test (ITT) AUC ( 72 )] and a decrease in fasting glycemia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 9 studies were conducted, with 8 studies conducted on preclinical models ( 70 78 ) and one study in humans ( 79 ) ( Table 4 ). The preclinical studies consistently reported positive effects of PBM on metabolic parameters with an improvement in glucose tolerance [with a glucose tolerance test area under the curve (GTT AUC) decreasing by 12–28%], a decrease in insulin resistance [with a 22% decrease in homeostatic model assessment of insulin resistance (HOMA-IR ( 70 )) and a 10% decrease in insulin tolerance test (ITT) AUC ( 72 )] and a decrease in fasting glycemia.…”
Section: Resultsmentioning
confidence: 99%
“…PBM also showed positive effects on lipid profiles with a reduction in free fatty acid, triglycerides and cholesterol levels. In the clinical study ( 79 ), PBM applied on eight muscles in patients with T2D resulted in a decrease in glycemia (fasting and 1h post-prandial glucose) observed 30 min to 12 h after PBM treatment. This decrease was evidenced by a reduction in the GTT AUC by 37% and a reduction of 1h postprandial glucose by 16%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation